Decoupling of Obsessions and Compulsions During Cognitive Behavioral Therapy for Youths With Obsessive Compulsive Disorder. (January 2022) - Olatunji, Bunmi O.; Cole, David; McGuire, Joseph F.; Schneider, Sophie C.; Small, Brent J.; Murphy, Tanya K.; Wilhelm, Sabine; Geller, Daniel A.; Storch, Eric A.
Although exposure and response prevention (ERP) is an effective treatment for obsessive compulsive disorder (OCD), it is unclear whether the decoupling of obsessions and compulsions is associated with treatment response. Accordingly, the present study examined change in the association between obsessions and compulsions during ERP for OCD as well as the association between decoupling of obsessions and compulsions and treatment outcome. The sample consisted of 140 youths with OCD who received 10 sessions of cognitive behavioral therapy with an emphasis on ERP. The findings show that the correlation and covariance of obsessions and compulsions increased during treatment. However, for participants that did not show improvement, the association between obsessions and compulsions strengthened over the course of treatment. In contrast, the association between obsessions and compulsions weakened over the course of ERP for treatment responders. These findings highlight the importance of the relationship between obsessions and compulsions in the treatment of OCD.